Rice cv. bahia mutagenized population: a new resource for rice breeding in the Mediterranean basin - Domingo, C.=700 1 Andres, F.; Talon, M.
(En, Es)
Ilus., 11 ref.
Keywords: ORYZA SATIVA; MUTACION; RADIACION; RADIACION GAMMA; VARIACION GENETICA; ESPAÑA